Factors relating to failure to quit smoking: a prospective cohort study - Azevedo, Renata Cruz Soares de; Fernandes, Rejane Firmino (São Paulo Medical Journal, 2011)
CONTEXT AND OBJECTIVE: Considering the difficulties in stopping smoking, this article aimed to identify factors relating to failure of attempts to quit smoking among smokers who sought care at an outpatient clinic in a general university hospital. DESIGN AND SETTING: Prospective cohort study evaluating 100 smokers who sought treatment at the Psychoactive Substances Outpatient Clinic. METHODS: The variables gathered were sociodemographic factors; degree of dependence (Fagerström questionnaire); stage of motivation for change (University of Rhode Island Change Assessment Scale); and presence of depression and anxiety (Hospital Anxiety and Depression Scale). The patients were followed up after 4, 8, 12 and 24 weeks to identify factors relating to failure to quit smoking. RESULTS: The patients were mostly women (75%), between 40 and 59 years of age (67%); with incomplete elementary education (60%); with leisure activities (57%); suffering from tobacco-related disease (53%); with previous attempts to quit smoking (70%); with a medical recommendation to stop (51%); with encouragement to stop (66%); and with a high degree of dependence (78%). The main motivational stage was contemplation/action (43%); the anxiety rate was 64% and the depression rate was 39%. The quitting rate was 66% among adherents and 17% among non-adherents (P < 0.001). Lack of success was correlated with absence of leisure, higher education and absence of tobacco-related disease. CONCLUSION: The variables of lack of leisure activities, higher education and/or lack of tobacco-related disease correlated with failure to quit smoking among smokers who sought treatment at an outpatient clinic in a tertiary general hospital.